Fundamental determinants of school efficiency and equity: german states as a microcosm for OECD countries - Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2007)
Cross-country evidence on student achievement might be hampered by omitted country characteristics such as language or legal differences. This paper uses cross-state variation in Germany, whose sixteen states share the same language and legal system, but pursue different education policies. The same results found previously across countries hold within Germany: Higher mean student performance is associated with central exams, private school operation, and socio-economic background, but not with spending, while higher equality of opportunity is associated with reduced tracking. In a model that pools German states with OECD countries, these fundamental determinants do not differ significantly between the two samples.
Keywords: I28; L38; L33; H52; D02; D63; J24; 330; Bildungsniveau; Bildungschancen; Bildungspolitik; Institutionalismus; Teilstaat; Deutschland